PENGARUH SEKTOR INDUSTRI PENGOLAHAN TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN MIMIKA - Firmansyah Firmansyah; Rochmatullah Rochmatullah (Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the impact of the processing industry sector on economic growth in Mimika Regency, Central Papua Province. The processing industry, particularly in gold and copper mining, plays a significant role in the regional economy, contributing substantially to local revenue and employment. However, the high reliance on this sector poses a risk of economic instability due to fluctuations in global commodity prices. This research utilizes a Systematic Literature Review (SLR) approach to explore the factors influencing the relationship between the processing industry sector and economic growth. The findings suggest that optimizing the processing industry sector requires adequate infrastructure, more advanced technology, and the development of local human resources. Additionally, the study highlights the importance of economic diversification as a strategy to reduce dependence on the mining sector, ensuring a more resilient economy. Sustainable development policies are also crucial to ensure long-term growth, as they can promote the responsible management of natural resources while enhancing local economic participation. The study recommends expanding the role of the processing industry beyond mining to include other sectors such as fisheries and forestry, which are underdeveloped yet promising. This research contributes to the formulation of strategies for fostering the sustainable development of the processing industry sector in Mimika Regency, thus helping to achieve inclusive economic growth while mitigating the risks associated with over-dependence on mining.